The Role of Education and Knowledge Science of Digital Era in The Perspective of Critical Thinking Teaching Method Norman Fairclough - Putri Retnosari; Rizal Mustansyir; Hastanti Widy Nugroho (Pancaran Pendidikan, 2019)
The research entitled " The Role Of Education And Knowledge Science of Digital Era In The Perspective of Critical Thinking Teaching Method Norman Fairclough" is motivated by challenges that bring together the increasingly complicated world of education and science in the digital age, only that there is something in accordance with the questionable model offered, which also attracts human interest in pseudo truth and information. The critical discussion method offered by Fairclough has opened new horizons for education and science so that it is not difficult to offer free sophistication and sophistication, because developments in the digital age are also recognized as having a negative impact on humans. This research is qualitative research using the literature method. Norman Fairclough, meanwhile the material objects used in this study are the basic concepts of research and research methods. After conducting a search in this study, the results obtained are (1) the formulation of critical thinking on the concepts of education and science (2) Finding education in the digital age by using five basic concepts that were initiated historical, power and ideology